Phytochemical Composition and Pharmaceutical Potential of Lantana sp: A Review (Asian Journal of Pharmaceutics (AJP), 2020)
Lantana is a common plant found in around 60 tropical and subtropical countries worldwide. It is a highlyinvasive species that has tremendously dominated over other species of plants and threaten biodiversity. Atpresent, physical, chemical, and biological agents are in consideration to eradicate this plant to prevent the threatto biodiversity and soil fertility. Lantana is considered as an unwanted plant and its biomass is disposed off. Inthis review, the pharmaceutical potential of this plant and its phytochemical constituents are discussed. Beingsource for wide variety of bioactive phytochemicals, Lantana is a valuable pharmaceutical raw material. Hence,instead of eradicating the plant as waste material, its pharmaceutical potentials such as antioxidant, antidiabetic,antimicrobial, anti-inflammatory, and anticancer activities can be exploited for the possible application astherapeutic agent. The modern medicine can take advantage of the fast-growing nature of this plant and use thisplant as a tool for biopharming. In traditional medicine, Lantana has been used in formulation along with otherplants as a treatment for several ailments. This review concludes that Lantana is a medicinally valuable plant, withhuge potential in the pharmaceutical industry.